Antimicrobial Activity and Cytotoxicity of Ag(I) and Au(I) Pillarplexes - Pöthig, Alexander; Ahmed, Sara; Winther-Larsen, Hanne Cecilie; Guan, Shengyang; Altmann, Philipp J.; Kudermann, Jürgen; Santos Andresen, Adriana Magalhães; Gjøen, Tor; Høgmoen Åstrand, Ove Alexander (Frontiers in Chemistry, 2018)
The biological activity of four pillarplex compounds featuring different metals and anions was investigated. The toxicity of the compounds against four bacterial strains (B. subtilis (ATCC6633), S. aureus (ATCC6538), E. coli (UVI isolate), P. aeruginosa), one fungus (C. albicans) and a human cell line (HepG2) was determined. Additionally, a UV-Vis titration study of the pillarplexes was carried out to check for stability depending on pH- and chloride concentration changes and evaluate the applicability in physiological media. All compounds are bioactive: the silver compounds showed higher activity against bacteria and fungi, and the corresponding gold pillarplexes were less toxic against human cells.